Unveiling the allelopathic potential of an endophytic bacteria from persicaria Orientalis (L.) Spach (Bangladesh Journal of Botany, 2026)
This study aimed to identify and evaluate the allelopathic potential of a bacterial isolate from Persicaria orientalis (L.) Spach. P. orientalis (Oriental Pepper) is known for its rapid growth and tolerance to various habitats, particularly near waste wetlands. Twenty morphologically distinct bacterial colonies were initially isolated, from which isolate E/29 was selected for comprehensive analysis. Based on colony morphology, Gram staining, and biochemical profiling, E/29 was preliminarily identified as Tatumella ptyseos. Molecular characterisation via 16S rRNA gene sequencing, however, revealed its identity as Stenotrophomonas maltophilia. Culture filtrates from S. maltophilia markedly improved seed germination. 100% seed germination observed in case of mung bean, 70% in rice, and 60% in case of field mustard compared to untreated controls. Additionally, the isolate significantly stimulated radicle and hypocotyl elongation across all three plant materials with the most pronounced effects in mung lentil (52.5 mm and 88.5 mm), followed by rice (~11 mm and 7.4 mm) and mustard (6.3 mm and 8.2 mm), demonstrating its potential as a bioinoculant for better agriculture.Bangladesh J. Bot. 55(1): 93-100, 2026 (March)